Pengenalan Deteksi Dini Kesehatan Mental Santri berbasis Sistem Informasi di Pondok Pesantren - Akas Yekti Pulih Asih; Maki Zamzam; Kuuni Ulfah Naila El Muna; Rizki Andikawati Fitriasari; Endang Sulistiyani (Universitas Nahdlatul Ulama Surabaya, 2023)
Roughly 5% of all teenagers in Indonesia are estimated to experience mental health disorders, yet only a small portion of them seek counseling or treatment. The rapid growth of Islamic boarding schools (Pondok Pesantren) in Indonesia, primarily catering to children and adolescents, has contributed to a vulnerable population regarding mental health issues. The dense schedule of students in pursuing both secular and religious knowledge, in addition to memorizing the Quran, coupled with the relatively low awareness and knowledge among the students, and the absence of early detection regarding mental health at the Sulaimaniyah Tahfidz Foundation in Surabaya, has become a particular concern. The introduction of early detection of mental health based on information systems called siskestren, is expected to address the existing issues at this partner institution. The community engagement project revealed an increase in mental health-related knowledge among the students. Moreover, six santri husada have been established and trained to conduct early detection of mental health using the siskestren system, enabling all santri husada to conduct mental health early detection on other students. By implementing siskestren at the Sulaimaniyah Tahfidz Foundation, it is hoped that it will raise awareness and knowledge among the students about their mental health condition and enable regular early detection of the students' mental health.